Resilient ℓ2-ℓ∞ filtering with dwell-time-based communication scheduling. (August 2020) - Sun, Ying; Ding, Derui; Dong, Hongli; Wei, Guoliang
Abstract: This paper is concerned with the resilient filtering problem for a class of discrete-time stochastic nonlinear systems with both time-varying delays and probabilistic distributed delays. In order to save the limited communication resource, stochastic communication protocols (SCPs) with multiple rules governed by a switching signal are employed to schedule the data transmission between the sensors and the filter for complying with different network scenarios and preserving the desired performance. An approach based on average dwell time (ADT) is utilized to establish the rule of SCPs for different scenarios. The purpose of the filtering problem is to design a resilient filter such that, under the regulation of SCPs, the dynamics of the filtering error is exponentially mean-square stable, and satisfies a prescribed disturbance attenuation level in a ℓ 2 - ℓ ∞ sense. A sufficient condition for the exponential mean-square stability is first derived and the ℓ 2 - ℓ ∞ performance is then guaranteed. In terms of certain linear matrix inequalities, the solvability of the addressed problem is discussed and the explicit expression of the desired resilient filter is also parameterized. Finally, a numerical example is provided to demonstrate the validity of the proposed design approach.